2005
DOI: 10.7589/0090-3558-41.1.96
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Infection in Farmed American Alligators (Alligator Mississippiensis) in Florida

Abstract: In September and October 2002, an epizootic of neurologic disease occurred at an alligator farm in Florida (USA). Three affected American alligators (Alligator mississippiensis) were euthanatized and necropsied, and results confirmed infection with West Nile virus (WNV). The most significant microscopic lesions were a moderate heterophilic to lymphoplasmacytic meningoencephalomyelitis, necrotizing hepatitis and splenitis, pancreatic necrosis, myocardial degeneration with necrosis, mild interstitial pneumonia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 29 publications
2
64
0
Order By: Relevance
“…Two groups of alligators from an alligator farm in Florida that had an outbreak of WNV (Jacobson et al, 2005) were used to validate an indirect ELISA to determine exposure of American alligators to WNV. Ten alligators (group 1) from a pen where alligators died during an outbreak of WNV in September to October 2002 were positive by ELISA, HAI, and PRNT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two groups of alligators from an alligator farm in Florida that had an outbreak of WNV (Jacobson et al, 2005) were used to validate an indirect ELISA to determine exposure of American alligators to WNV. Ten alligators (group 1) from a pen where alligators died during an outbreak of WNV in September to October 2002 were positive by ELISA, HAI, and PRNT.…”
Section: Discussionmentioning
confidence: 99%
“…In September and October 2002, a large commercial alligator farming operation in Florida (28Њ32ЈN, 80Њ56ЈW) had an epizootic of central nervous system disease in alligators up to 2 yr of age (Jacobson et al, 2005). Approximately 2 mo after the epizootic ended, 10 alligators from a pen where deaths occurred (group 1) and 10 from a pen where there were no deaths (group 2) were moved into separate pens.…”
Section: Alligators and Serum/plasma Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain aspects of the biology of WNV facilitate its ability to cause severe disease. WNV productively infects diverse cell populations from many animal species, suggesting usage of multiple and/or well-conserved receptors (9,53,58,79,157,178,195). The relatively diverse tropism of WNV allows viral replication in several tissues in animal and human hosts and may contribute to the wide spectrum of clinical manifestations (76,142,167,199).…”
Section: Viral and Host Factors That Modulatementioning
confidence: 99%
“…4,5,6 Furthermore, the findings in WNV infection of alligators and other aquatic animals suggested that contaminated environment, including food or water, may contribute to the spread of WNV. 8 Although wild and domestic turkeys are not generally recognized as susceptible to WNV, individual variation in susceptibility and immune status may alter risk for infection. Such is true with mammalian species that are generally resistant to the disease, but infections in humans, horses, squirrels, cows, and dogs have been reported.…”
mentioning
confidence: 99%